UM MÉTODO PARA ELICITAÇÃO E MODELAGEM DE REQUISITOS BASEADO EM OBJETIVOS - CARVALHO, Márcia Cristina Ferro (2002)
This work proposes an integration of the approach CREWS L ecritoire based on scenarios with the approach of use cases described by Regnell & al and the Method GBRAM. In this case, the work of Regnell is extended with the notion of Requirement Chunk (RC), strategies for discovering objectives through the relationships AND, OR, and refinement between RCs, as well as extending the model with a physical level where the internal actions of the system are described. On the other side, the approach CREWS L ecritoire is extended with coupling of objective and use case where the scenarios are obtained by applying a strategy of refining use cases, and also with an integration of normal and exceptional scenarios in one synthetic model of use with one unique vision for each actor. The Method GBRAM is extended with the alternative contract dependency, composicional contract dependency, inclusive and exclusive contract dependency, as well it introduzed the use case technique, described by Regnell et al and extended with the notion of scenarios for caracterize exceptionals, variationals and normal situations. With the integration of threes methods, the new method which benefit from the advantages of the approaches of CREWS-L ecritoire, use cases.and goals. The new method proposes a coupling between objective and Use Cases in a top-down decomposition of different levels of abstraction. The method combines the two concepts into a Requirement Chunk (RC). An RC is a pair of <objective, Use Case> related with AND, OR and refinement. These three types of relations between RCs lead to a hierarchic organisation of RCs in three levels of abstractions: functional, behaviour, and physical.